2000
DOI: 10.1093/intimm/12.3.397
|View full text |Cite
|
Sign up to set email alerts
|

B cell development and activation defects resulting in xid-like immunodeficiency in BLNK/SLP-65-deficient mice

Abstract: Engagement of the B cell receptor (BCR) leads to the activation of tyrosine kinases and other signaling molecules that ultimately determine the type and magnitude of the B lymphocyte's cellular response. The adaptor protein BLNK/SLP-65 plays a pivotal role in BCR signal transduction by coupling Syk activation to downstream elements such as Grb2, phospholipase C-gamma, Vav and Nck. We have generated BLNK(-/-) mice to determine the physiological role of this protein in B cell development and activation. BLNK(-/-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
111
0
1

Year Published

2001
2001
2010
2010

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(116 citation statements)
references
References 35 publications
4
111
0
1
Order By: Relevance
“…In separate studies, we have shown that at least two components of the BCR signalosome, BTK and PLC-␥2, are required for the activation of NF-B and transcriptional up-regulation of the bcl-x gene (58), 2 further supporting an involvement of the BCR signaling in T2 B cell responses. Like BTK and PLC-␥2, other components of the BCR signalosome including phosphatidylinositol 3-kinase, Vav, and B cell linker protein are involved in the transition of immature B cells to more mature stages (27,28,40,(42)(43)(44)(45). The opposite biological responses of T1 versus T2 and an involvement of the BCR signaling components in this process is also supported by a recent study published during the preparation of this manuscript (65).…”
Section: Discussionsupporting
confidence: 62%
“…In separate studies, we have shown that at least two components of the BCR signalosome, BTK and PLC-␥2, are required for the activation of NF-B and transcriptional up-regulation of the bcl-x gene (58), 2 further supporting an involvement of the BCR signaling in T2 B cell responses. Like BTK and PLC-␥2, other components of the BCR signalosome including phosphatidylinositol 3-kinase, Vav, and B cell linker protein are involved in the transition of immature B cells to more mature stages (27,28,40,(42)(43)(44)(45). The opposite biological responses of T1 versus T2 and an involvement of the BCR signaling components in this process is also supported by a recent study published during the preparation of this manuscript (65).…”
Section: Discussionsupporting
confidence: 62%
“…We and others have previously demonstrated that BTK deficiency leads to a severe mature FoB cell deficiency, despite intact T2 and mature MZ B cell subsets, termed Xid (xid) in mice (19 -22). An xid-like phenotype is also observed in animals with gene-targeted deletion of PLC-␥2, which is a direct target of BTK, and B cell linker protein (BLNK), an adaptor which facilitates BTK and PLC-␥2 interaction (23)(24)(25)(26)(27). These observations support an active role for BCR signaling, particularly the BTK/PLC-␥2 signaling axis, in the differentiation of T2 into mature FoB cells (3,4,15,25,26,28).…”
mentioning
confidence: 71%
“…To determine the mechanisms underlying these complex functions will require identification of the specific molecules and domains responsible for receptor trafficking. As deletion of BLNK impairs B cell development (53)(54)(55), studies in deficient mice are likely to be unrevealing.…”
Section: Discussionmentioning
confidence: 99%